Effect of postharvest sodium benzoate treatment on some fruit parameters of two organic apple cultivars - Molnár, B.; Szabó, Sz.; Veres, Á.; Holb, I. J. (International Journal of Horticultural Science, 2020)
The aim of this study was to investigate the effect of postharvest sodium-benzoate treatment on some fruit parameters of two organic apple cultivars (’Topaz’ and ’Florina’). Assessments were made at three times during storage: 17 November 2019, 20 December 2019 and 23 January, 2020. During every assessment dates, each fruit was observed separately, and determined the proportion of i) healthy fruits (%), ii) post-harvest fruit rot diseases iii) fruits with mechanical injury (%), iv) fruit with russetting (%), v) damage of codling moth and vi) Ca-deficiency symptoms. In addition, fruit weight (g) was measured at each assessment date. Sodium benzoate reduced the fruit decay and the proportion of healthy fruit was higher in this treatment compared to water treated fruit. This effect could be seen in all assessment dates and on both cultivars. Effects on other parameters were various according to cultivar and assessment dates. Loss of fruit weight was similar in both treatments and cultivars compared to control treatment.